2009
DOI: 10.1002/lt.21687
|View full text |Cite
|
Sign up to set email alerts
|

Usage and outcomes of deceased donor liver allografts with preprocurement injury from blunt trauma

Abstract: The use of extended criteria donors is an effective way of reducing the shortage of deceased donor organs. Evidence of significant liver trauma in a deceased donor usually rules out transplantation of the liver. The aim of this study was to evaluate the use and outcomes of donor livers with preprocurement trauma. Records of all 312 deceased donors with a history of trauma between January 1986 and September 2007 were reviewed. Donors with macroscopic liver injuries were identified, and data from recipient medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…It is unclear from the study by Geenen et al 1 why so few donor livers had evidence of contusion/hematoma. A likely explanation is that such injuries may go unno-ticed at the time of retrieval or indeed the back-table dissection, particularly in the absence of capsular damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear from the study by Geenen et al 1 why so few donor livers had evidence of contusion/hematoma. A likely explanation is that such injuries may go unno-ticed at the time of retrieval or indeed the back-table dissection, particularly in the absence of capsular damage.…”
mentioning
confidence: 99%
“…Geenen et al 1 suggested that these livers should undergo resection of the injured area of the graft, either on the back-table or as an in situ split. Although the former option could be indicated in severe injuries with significant capsular damage, the latter is likely to be the exception rather than the norm in the setting of an unstable donor, who would require packing and an expedited procedure.…”
mentioning
confidence: 99%
“…126,127 Depending on the nature and grade of injury, extensive backtable treatment-including vas cular repair or lobe resection-might be necessary prior to organ implantation. A thorough backtable investiga tion for occult vascular lesions is important, and biliary lesions can be ruled out with cholangiography during this procedure.…”
Section: Unusual Donor Selectionmentioning
confidence: 99%
“…3 However, limited reports exist on the use of injured livers for LT. 2,[4][5][6][7][8] Many centers consider traumatized grafts a contraindication for LT, mainly because of high-grade lacerations; consequently, several of these donors are commonly declined. 9 We report the case of a successful LT performed using a high-grade lacerated liver previously treated with a super-selective arterial embolization for bleeding control.…”
Section: Introductionmentioning
confidence: 99%